Pedagogical modernization or political assimilation? The 1879 elementary education act in the mirror of parliamentary debates and Néptanítók Lapja - Kéri, Katalin (Central European Journal of Educational Research, 2026)
Act XVIII of 1879, which mandated the teaching of the Hungarian language in all elementary schools across Hungary, represented a decisive turning point in the educational structure of the Austro-Hungarian Monarchy. Drawing upon the theoretical frameworks of Ernest Gellner (1983) and Eugen Weber (1976), this research focuses on how state-driven linguistic homogenization emerged simultaneously as a professional necessity and a tool of nation-building. Our study presents the content of the act and the pro et contra arguments within the parliamentary debates surrounding its adoption. Furthermore, it highlights the core concepts and elements of the official pedagogical discourse following the legislation through a qualitative thematic analysis of the 1879 issues of Néptanítók Lapja (People’s Teachers’ Gazette), a government-sponsored weekly professional journal. Our findings reveal an inherent contradiction in the official rhetoric: while the journal promoted innovative, communication-centered “natural methods” in language instruction, these pedagogical advancements primarily served to consolidate political loyalty and erode minority national identities. The analysis identifies three main discourse types: the professionalization of the “Magyarization” process, the ideological construction of the Hungarian language as a “civilizational” prerequisite for social mobility, and the practical challenges faced by rural educators working in multilingual environments. By placing the Hungarian case within a broader European comparative perspective, the study contributes to the understanding of how 19th-century school systems functioned as arenas for national identity construction in multiethnic regions.